Clinical outcome of the off-pump coronary artery bypass surgery- a comparison between combined high thoracic epidural anaesthesia with GA and GA alone (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: The common challenges for the cardiac anaesthesiologist during off pump coronary artery surgery (OPCAB) include haemodynamic stability during the different stressful surgical events and multiple cardiac manipulations, providing adequate myocardial protection, and obtaining effective postoperative analgesia leading to early discharge from the intensive care unit. Objective: This study has been undertaken with a view to find out whether a combined high thoracic epidural anaesthesia (HTEA) with general anaesthesia (GA) is safe and more efficient in providing overall cardiovascular stability as well as improving the parameters leading to a better outcome in terms of a shorter and more predictable road maps to recovery. Methods: Sixty patients aged within 40-70 years, without having any coagulopathy disorder, any emergency surgery or left main disease scheduled for CABG on beating heart were enrolled in prospective, randomized observational comparative study. Patients were divided in two groups. In group A patients received GA alone and in group B patients received high thoracic epidural anaesthesia with GA. The parameters including heart rate, SPO2, CVP, arterial blood pressure, ECG, and ABG analysis were recorded before induction, during induction, intubation and during different events of the surgery. Post operative pain score, sedation score, ventilator hour, duration in the ICU stay,  rescue analgesic need and post operative complications was assessed and recorded. Results: significant per-operative mean heart rate changes were observed all the events except at wound closure and during anastomosis with D1/D2 and the mean difference of mean arterial pressure at intubations, skin incision, sternotomy, pericardiotomy, during anastomosis of distal end of the graft with RCA, PDA, LCX and D1/D2 were observed statistically significant (p